(NvAN(B-(NkRISTOF(B: [(NrOMAN(B];s (NkNIGA (B4; (NkNIGA (B5 /s (N~ASTX (B2s - (NrOLLAN(B, (NrOMENs ((NmOSKWA(B:s (NpRAWDA(B,s, 1982)
(Nw NASTOQ]IJ TOM ROMANA (B"(NvAN(B-(NkRISTOF(B", (NSOZDANNOGO ZAME^ATELXNYM FRANCUZSKIM PISATELEM rOMENOM rOLLANOM (B(1866 - 1944) (NWO[LI ^ETWERTAQ I PQTAQ KNIGI (B- "(NbUNT(B", "(NqRMARKA NA PLO]ADI(B".s
"(NbUNT(B", "(NqRMARKA NA PLO]ADI(B"s
rus
Keywords: (NkLASSI^ESKAQ PROZAs; (NrOMANs